Genetic variability of rumen Selenomonads - Pristas, P; Piknova, M; Sprincova, A; Javorsky, P (Folia microbiologica, 2008)
Molecular diversity of rumen bacteria belonging to the species Selenomonas ruminantium was evaluated by biochemical and PCR analyses targeted at the 16S rRNA operon and lactate dehydrogenase gene. While extremely variable in metabolic characteristics, two different RISA (ribosomal intergenic spacer analysis), and five lactate dehydrogenase gene RFLP profiles were observed among the twelve strains studied. The strains showed very limited variability ARDRA ( amplified ribosomal DNA restriction analysis) when two different profiles were observed only. 16S rDNA sequence comparisons indicate complex genetic structure within S.ruminantium population.
Keywords: vysoká zvěř; polymorfismus délky restrikčních fragmentů; Animals; molekulární sekvence - údaje; ribozomální DNA; Deer; L-Lactate Dehydrogenase; bakteriální proteiny; DNA bakterií; DNA, Bacterial; Molecular Sequence Data; Polymorphism, Restriction Fragment Length; RNA ribozomální 16S; Bacterial Typing Techniques; genetická variace; Bacterial Proteins; bachor; RNA, Ribosomal, 16S; Rumen; zvířata; fylogeneze; DNA, Ribosomal; L-laktátdehydrogenasa; Phylogeny; Veillonellaceae; Genetic Variation; techniky typizace bakterií